Ebstein malformation Diagnostic Catheter - electrode - Domínguez M., Pedro (1968)
The case of a 16 years-old patient with a mild from of Ebstein{s malformation of the tricuspid valve is presented. The disease was discovered on account of an infectious illness for which the patient came to the hospital. The diagnosis was made on clinical, radiologic and electrocardiographic grounds, and confirmed by the intracavitary electrocardiography in the diagnosis of this disease.